Analysis of Health Cadre Performance on Toddler Mother Compliance to Integrated Health Posts and Growth and Development Detection in the Work Area of Pon Village Health Center, Sei Bamban District, Serdang Bedagai Regency in 2025 - Rumapea, Fina; Karnirius Harefa; Teja Kesuma (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Cadre performance reflects the effectiveness of cadres in fulfilling their assigned duties and responsibilities. Poor compliance of mothers of toddlers in attending Posyandu and participating in growth and development monitoring has led to two cases of malnutrition, 20 cases of severe malnutrition, and 10 cases of stunting. Improving maternal compliance can help address these issues. Objective: This study aimed to analyze the relationship between health cadre performance and maternal compliance with Posyandu visits and toddler growth and development monitoring. Methods: The study involved 86 mothers of toddlers selected through purposive sampling. A quantitative analytical design was used, with data collected via a validated and reliable questionnaire. Data were analyzed using factor analysis techniques. Results: There was a significant relationship between health cadre performance and maternal compliance with Posyandu visits (p < 0.05), as well as a significant relationship between cadre performance and growth and development detection among toddlers in the working area of Pon Village Health Center, Sei Bamban District, Serdang Bedagai Regency, in 2025 (p < 0.05). Conclusion: Health cadre performance is significantly associated with maternal compliance to Posyandu visits and toddler growth and development detection. It is recommended that cadres enhance service quality, particularly in monitoring growth and development through routine child monitoring and providing education on child health and the risks of malnutrition.